2014
DOI: 10.1038/srep06003
|View full text |Cite
|
Sign up to set email alerts
|

Graphene on Mica - Intercalated Water Trapped for Life

Abstract: In this work we study the effect of thermal processing of exfoliated graphene on mica with respect to changes in graphene morphology and surface potential. Mild annealing to temperatures of about 200°C leads to the removal of small amounts of intercalated water at graphene edges. By heating to 600°C the areas without intercalated water are substantially increased enabling a quantification of the charge transfer properties of the water layer by locally resolved Kelvin probe force microscopy data. A complete rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
77
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 52 publications
(64 reference statements)
6
77
0
1
Order By: Relevance
“…Note that in some cases carbon monoxide can intercalate between the substrate and graphene, which is for example the case of graphene/Pt(111) or graphene/Ir(111) systems at partial CO pressure ( p > 1×10 −6 mbar). Intercalation of water molecules at room temperature was also reported after exposure to ambient conditions . Intercalated water between graphene and Cu(111) can induce graphene fragmentation at line defects .…”
Section: Resultsmentioning
confidence: 85%
“…Note that in some cases carbon monoxide can intercalate between the substrate and graphene, which is for example the case of graphene/Pt(111) or graphene/Ir(111) systems at partial CO pressure ( p > 1×10 −6 mbar). Intercalation of water molecules at room temperature was also reported after exposure to ambient conditions . Intercalated water between graphene and Cu(111) can induce graphene fragmentation at line defects .…”
Section: Resultsmentioning
confidence: 85%
“…To measure the thickness of the sheets, we conducted tappingmode atomic force microscopy (AFM) on an air-dried graphene residue, where a myriad of sheets with thicknesses less than 1 nm (described in previous reports as single-layer graphene 36,37 ) was observed on a mica substrate ( Fig. 3d and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al have demonstrated in their pioneering work 8 that water can be aggregated between a mica substrate and a graphene sheet on top. Water intercalation between graphene (cover) and mica (substrate) have recently received tremendous attention [9][10][11][12][13][14][15][16][17][18] . Such intercalated water is in contact with the environment through defects in the graphene cover, which we will further refer to as B-defects 9 .…”
mentioning
confidence: 99%